2019
DOI: 10.1097/shk.0000000000001255
|View full text |Cite
|
Sign up to set email alerts
|

Toll Like Receptor 4 Mediated Lymphocyte Imbalance Induces Nec-Induced Lung Injury

Abstract: Necrotizing enterocolitis (NEC) is the leading cause of death from gastrointestinal disease in premature infants, and is associated with the development of severe lung inflammation. The pathogenesis of NEC-induced lung injury remains unknown, yet infiltrating immune cells may play a role. In support of this possibility, we now show that NEC in mice and humans was associated with the development of profound lung injury that was characterized by an influx of Th17 cells and a reduction in Tregs. Importantly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…It has been reported that IL-17 is critical in mediating pulmonary neutrophil infiltration, whereas the lungs encountered infectious insults (40)(41)(42)(43)(44). Our previous studies in necrotizing enterocolitisinduced lung injury also indicated that IL-17 is critical in neutrophilic lung inflammation (45). Thus, we hypothesized that IL-17-mediated neutrophil influx is, at least in part, the underlying mechanism by which ACE2 modulates neutrophilic inflammation in bacterial lung infection.…”
Section: Ace2 Regulates Il-17-mediated Neutrophil Infiltration By Modmentioning
confidence: 84%
“…It has been reported that IL-17 is critical in mediating pulmonary neutrophil infiltration, whereas the lungs encountered infectious insults (40)(41)(42)(43)(44). Our previous studies in necrotizing enterocolitisinduced lung injury also indicated that IL-17 is critical in neutrophilic lung inflammation (45). Thus, we hypothesized that IL-17-mediated neutrophil influx is, at least in part, the underlying mechanism by which ACE2 modulates neutrophilic inflammation in bacterial lung infection.…”
Section: Ace2 Regulates Il-17-mediated Neutrophil Infiltration By Modmentioning
confidence: 84%
“…Although intestinal damage is the most significant contributor to illness in patients with NEC, these children also experience damage to peripheral organs, including the lungs and brain. 30,65,66 Remote organ injury in neonates with NEC occurs in part through the release of TLR4 ligands from the damaged gut, including high mobility group box 1 (HMGB1), which is released from dying intestine into the circulation, where it causes injury to both the lung and brain, through pathways that are incompletely understood. 30,67 It is noteworthy that HMGB1 also has been shown to form a complex with bacterial lipids during inflammation, which can trigger RIPK3-dependent immune responses, 68 suggesting the possibility that HMGB1 release also may induce necroptosis in these other organs.…”
Section: Discussionmentioning
confidence: 99%
“…NEC-induced lung injury is particularly severe as compared to the lung injury that develops in premature infants who do not develop NEC. We have shown that TLR4 expression on the lung epithelium is required for the recruitment of proinflammatory neutrophils into the lung through the upregulation of CCL25 (50,51), and that strategies to either inhibit TLR4 via the administration of aerosolized inhibitors, or through genetic deletion, can serve as novel lung protective strategies in the setting of NEC (50).…”
Section: Physical Epithelial Barriers Associated Signaling and The mentioning
confidence: 99%